Evaluasi Kinerja Guru - Maharani; Nova, Geri Anti; Putri Endang, Aulia Zahra (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Teacher performance evaluation is an important instrument in efforts to improve the quality of education. This study aims to evaluate teacher performance by focusing on the model and practice of minimal teacher performance. This study is relevant considering the importance of the role of teachers in the learning process and the demands for improving the quality of education. This study uses a qualitative approach with a literature study method. The subjects of the study were a number of teachers from various levels of education. Data collection was carried out through document analysis from various articles related to teacher performance evaluation. The results of the study indicate that the models and practices of teacher performance applied still vary. Some teachers have implemented innovative learning models and actively involved students. However, there are still many teachers who tend to use conventional learning methods. In addition, the practice of teacher performance assessments that are carried out also still needs to be improved. Based on the results of the study, it can be concluded that efforts are needed to improve teacher performance through various strategies. Some recommendations that can be given include the development of ongoing training programs for teachers, the provision of adequate learning facilities and infrastructure, and the development of a more objective and accountable teacher performance assessment system. Thus, it is hoped that the quality of learning can improve and national education goals can be achieved.